2019
DOI: 10.1167/iovs.18-24850
|View full text |Cite
|
Sign up to set email alerts
|

Automated Measurement of Tear Meniscus Height with the Kowa DR-1α Tear Interferometer in Both Healthy Subjects and Dry Eye Patients

Abstract: PURPOSE. To develop and assess a method for quantitation of lower tear meniscus height (TMH) with the Kowa DR-1a tear interferometer. METHODS. Sixty-nine eyes of 49 men and 20 women (36 healthy volunteers, 33 patients with aqueous-deficient dry eye [ADDE]; mean age 6 SD, 50.0 6 14.0 years) were enrolled. TMH of each subject was measured by two observers both with DR-1a and newly developed software and with anterior-segment swept-source optical coherence tomography (SS-OCT). Intraoperator repeatability and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 32 publications
5
16
0
Order By: Relevance
“…Although we found a lower Schirmer test in the PSS and SSS groups (8.478 ± 9.610 and 7.778 ± 7.345 mm, respectively), it was within normal range in the allergic group as previously reported (16.348 ± 8.947 mm) 38,39. These results associated with the lack of repeatability and sensibility of the Schirmer test might have contributed to the absence of difference between the MGD and non-MGD group and the discordant result with TMH 49,50. Similarly, no significant difference was observed between MGD and non-MGD groups regarding BUT, NIKBUTf, or NIKBUTavg.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Although we found a lower Schirmer test in the PSS and SSS groups (8.478 ± 9.610 and 7.778 ± 7.345 mm, respectively), it was within normal range in the allergic group as previously reported (16.348 ± 8.947 mm) 38,39. These results associated with the lack of repeatability and sensibility of the Schirmer test might have contributed to the absence of difference between the MGD and non-MGD group and the discordant result with TMH 49,50. Similarly, no significant difference was observed between MGD and non-MGD groups regarding BUT, NIKBUTf, or NIKBUTavg.…”
Section: Discussionsupporting
confidence: 81%
“…Tear fluid secretion, Schirmer, and TMH are supposed to be increased in patients with MGD as a compensatory mechanism to lipid layer deficiency in order to stabilize the tear film, whereas tear secretion, Schirmer, and TMH are decreased in PSS and SSS 46,47. Despite its limitations, Schirmer test is a common method for evaluation of lacrimal gland secretion function 48,49. In this study, the Schirmer test was normal in both the MGD and the non-MGD group.…”
Section: Discussionmentioning
confidence: 99%
“…LLT, TMH, NIBUT, tear interference, and subjective symptoms were sequentially measured both just before as well as 30, 60, and 90 min after administration as follows: (1) LLT of each eye was quantified with the LipiView instrument 49 . (2) TMH 56 , NIBUT, and tear interference pattern 10 for each eye were determined with the DR-1α tear interferometer (Kowa, Aichi, Japan) 57,58 . Each eye was assigned to one of three classes on the basis of the combination of interferometric pattern and NIBUT: class 0 (normal type: monotonous gray or multicoloured interferometric fringe with a stable tear film [NIBUT of ≥5 s]), class 1 (ADDE type: multicoloured interferometric fringe and an unstable tear film [NIBUT of <5 s], corresponding to insufficient tear fluid but a thick lipid layer), and class 2 (EDE type: grayish amorphous interferometric image without a fringe and an unstable tear film [NIBUT of <5 s], corresponding to a thin lipid layer but sufficient tear fluid), as previously described 10 .…”
Section: Methodsmentioning
confidence: 99%
“…Goto et al [ 92 ] developed a tear interference color chart for the DR-1 α interferometer (Kowa, Nagoya, Japan), which can be useful for converting tear interference color information to the lipid layer thickness (LLT) [ 92 ]. Subsequently, Arita et al [ 93 ] showed that the DR-1 α interferometer could measure the TMH as reliably as SS-OCT and showed that the interferometric TMH had correlation with Schirmer's score. Arita et al [ 88 ] also described a difference in interferometric patterns among aqueous-deficient DED, MGD, and normal control on the DR-1 α interferometry, suggesting that the device can be helpful for differential diagnosis of subtypes of DED.…”
Section: Interferometrymentioning
confidence: 99%